The Indian in the cupboard [videorecording (DVD)] - Oz, Frank; Scardino, Hal; Davis, G. Paul, 1969-; Crouse, Lindsay; Jenkins, Richard, 1947-; Bhat, Rishi; Coogan, Steve; Keith, David, 1954-; Banks, Lynne Reid, 1929- (Columbia TriStar Home Entertainment, 2004)
On his 9th birthday, Omri receives a cupboard that magically brings his toy Indian Little Bear to life. They bond, embarking on an amazing adventure, until Omri's friend Patrick brings a 6-shooting cowboy to life and the secret of the cupboard is in danger of being revealed.